A Scalable Large Format Display Based on Zero Client Processor - Sang Don Kim; Seung Eun Lee (Institute of Advanced Engineering and Science, 2015)
This paper proposes zero client module that targets Large Format Display (LFD) system for display wall. Increased resolution in modern LFD requires a high bandwidth channel and a high performance display controller to transfer the image data to the monitor. The key idea is to use a Gagabit-Etherent communication based Daisy-Chain to transfer an image data. This communication supports sufficient bandwidth for image data transfer. As a result, we implement the LFD system using tha zero client module and LFDmonitors.